MENGEMBANGKAN MULTIPLE INTELLIGENCES DENGAN BERMAIN PADA ANAK USIA DINI - Alfien Baddrin Afdhilla; Syarizal Agam Mahendra (Jurnal CARE (Children Advisory Research and Education), 2020)
AbstractMultiple Intelligencesis an intelligence theory that has rejected traditional theories before, namely refusing to use IQ as a person's intelligence score. Multiple Intelligences in the form of mathematical logical intelligence, visual spatial, physical kinesik, musical, interpersonal, intrapersonal, linguistic and natural. This intelligence is very important to be developed in children from an early age. The purpose of this study is to analyze how multiple intelligences can be developed through play in early childhood. With this research parents can recognize the intelligence of children and even direct and develop intelligence optimally. This research is a qualitative research with a literature study. Using Miles Huberman's data analysis technique Interactive Analysis to draw conclusions. The results of this study are that playing can improve the development of children's multiple intelligences. Because playing can develop cognitive aspects, abstract thinking, creative thinking, social-emotional, motor, language or communication, and can also develop creativity.Keywords: Multiple Intelligence, Play, Early ChildhoodAbstrakMultiple Intelligences merupakan teori kecerdasan yang telah menolak teori tradisional sebelumnya, yakni menolak menggunakan IQ sebagai skor kecerdasan seseorang. Multiple Intelligences berupa kecerdasan logis matematis, visual spasial, kinesik jasmani, musikal, interpersonal, intrapersonal, linguistik dan natural. Kecerdasan tersebut sangat penting dikembangkan pada anak sejak usia dini. Tujuan penelitian ini adalah menganalisis bagaimana multiple intelligences dapat dikembangkan melalui bermain pada anak usia dini. Dengan penelitian ini orang tua dapat mengenal kecerdasan anak bahkan mengarahkan dan mengembangkan kecerdasan secara maksimal. Penelitian ini merupakan penelitian kualitatif dengan studi kepustakaan. Menggunakan teknik analisis data milik Miles Huberman yakni Analisis Interaktif untuk menarik kesimpulan. Hasil dari penelitian ini adalah bermain dapat meningkatkan perkembangan kecerdasan majemuk anak. Karena bermain dapat mengembangkan aspek kognitif, berpikir abstrak, berpikir kreatif, sosial-emosional, motorik, bahasa atau komunikasi, dan dapat pula mengembangkan kreativitas.Kata Kunci: Kecerdasan Majemuk, Bermain, Anak Usia Dini